Basin closure and environmental flow requirements - Smakhtin, Vladimir U. (2008)
A river basin is referred to as 'closed' when all its river flow is allocated to different uses. Water requirements of freshwater-dependent ecosystems, often referred to as 'environmental flow requirements', only recently started to receive attention. This 'user' is still often neglected in river basin management. This paper discusses the place of environmental flow requirements in basin water resources, examines a global pattern of closed/closing river basins and advocates the need to set environmental requirements in advance of major basin developments. It is also suggested that to ensure sustainable water resources development in the future, it is necessary to revise the content of 'basin closure' by explicitly introducing environmental flow requirements into basin water management and supporting it with relevant policies.